2011
DOI: 10.1590/s0100-29452011000500097
|View full text |Cite
|
Sign up to set email alerts
|

Alterações nos teores nutricionais foliares de bananeira 'prata-anã' adubada com composto orgânico em cinco ciclos de produção

Abstract: O presente trabalho objetivou avaliar o estado nutricional da bananeira-'Prata-anã' durante cinco ciclos de cultivo com adubação orgânica, no município de Botucatu-SP. As plantas foram adubadas com composto orgânico produzido a partir de serragem de madeira e esterco bovino, em que os tratamentos foram constituídos de doses desse composto (0; 98,5; 197,0; 290,5 e 394,0 g de K2O/planta). Empregou-se delineamento experimental em blocos casualizados, com cinco tratamentos e cinco repetições. No florescimento das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…These differences indicate an overall decrease in sufficiency ranges. Analogously, Urano et al (2007) and Deus et al (2018) reported narrower normal ranges than those found in the literature; Accordingly, these region-specific methods should be considered more accurate by decreasing soil and climate variation effects, i.e., in accordance with the farm's production capacity. This prevents misleading extrapolations and mistakes when transferring knowledge; simply put, different environments, different managements (RESENDE et al, 2017).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…These differences indicate an overall decrease in sufficiency ranges. Analogously, Urano et al (2007) and Deus et al (2018) reported narrower normal ranges than those found in the literature; Accordingly, these region-specific methods should be considered more accurate by decreasing soil and climate variation effects, i.e., in accordance with the farm's production capacity. This prevents misleading extrapolations and mistakes when transferring knowledge; simply put, different environments, different managements (RESENDE et al, 2017).…”
Section: Resultsmentioning
confidence: 68%
“…Multivariate compositional nutrient diagnosis (CND) indices developed by Raghupathi et al (2002) were instrumental in diagnosing P and Zn imbalances caused by changes in N and K concentrations in Robusta (AAA) and Ney Poovan (AB) cultivars of banana. Although P is more available in the soil, P leaf concentration remains virtually unchanged (DAMATTO JUNIOR et al, 2011), even among cultivars of different subgroups (BORGES et al, 2006).…”
Section: Resultsmentioning
confidence: 99%